Is hospital blood glucose monitoring on track? - Begley, Andrea (Wiley-Blackwell, 2016)
Inpatient blood glucose monitoring (BGM) is considered a cornerstone of diabetes management. Maintaining best practice BGM in hospital enables healthcare providers to monitor the efficacy of treatment regimes and guide adjustments. Strict nursing adherence to site-specific BGM policy is imperative to optimise treatment outcomes. The aim of this research was to ascertain staff awareness of site BGM policy and assess current practice. This is a single-centre observational study within a secondary hospital using mixed methods data collection and purposeful selection. A quantitative survey (n = 77) investigating nursing knowledge of hospital BGM policy on testing frequency and timing revealed a gap between staff perception of policy awareness (88%) and accuracy of actual knowledge (67% for type 1 diabetes and 47% for type 2 diabetes). Medical record documentation of patient blood glucose levels (BGLs) (n = 102) was reviewed to compare nursing BGM practices against policy. Adherence to BGM policy varied significantly; only 10–44% of insulindependent patients had BGLs tested within 30 minutes before meals as recommended. Furthermore, only 59% of patients (n = 94) had BGLs checked four times daily for 72 hours from admission as outlined in the policy. Fifteen nurses took part in the focus groups and responses were reviewed using constant comparison techniques and thematically analysed. Barriers affecting best practice BGM included delays in meal delivery and time constraints requiring prioritisation of other clinical duties over BGM. Results indicate that further work, including a structured education program for nurses and review of the meal delivery process, is recommended to improve BGM practices.